Effects of alcohol withdrawal on monocyte subset defects in chronic alcohol users. Issue 5 (2nd June 2016) - Donnadieu‐Rigole, Hélène; Mura, Thibault; Portales, Pierre; Duroux‐Richard, Isabelle; Bouthier, Martine; Eliaou, Jean‐Francois; Perney, Pascal; Apparailly, Florence
Abstract : Chronic alcohol use alters the distribution and the phenotypic and functional characteristics of blood monocyte subsets, which are partially restored following 2 wks of withdrawal. Abstract : Excessive alcohol consumption has a modulating effect on immune functions that may contribute to decreased immunity and host defense. It is associated with increased intestinal permeability to endotoxins that is normalized after 14 d of abstinence. Whether and how blood monocyte subsets are impaired in patients with an AUD and what their evolution is after alcohol withdrawal are the paper's objectives. With the use of flow cytometry, blood monocyte subsets were quantified in AUDs before ( n = 40) and 2 wk after ( n = 33) alcohol withdrawal and compared with HC donors ( n = 20). Expression of TLR2 and TLR4 on monocyte subsets was also quantified. Cytokine response of monocytes was monitored following PGN and LPS stimulation. The CD14 + CD16 − subset was decreased, whereas the CD14 dim CD16 + subset was expanded ( P < 0.001) in AUD compared with HC. The frequencies of TLR2‐ and TLR4‐expressing monocytes were reduced in AUD compared with HC. Although the basal production of IL‐1, IL‐6, and TNF by monocytes in AUD was compared with HC, the PGN‐ and LPS‐mediated IL‐6 and TNF production was increased in AUD. Frequencies of IL‐6‐expressing monocytes were higher in AUD than HC. Alcohol withdrawal partially restored the distribution of monocyte subsets and the frequency of IL‐6‐producing monocytes and increased the frequency of TNF‐producing cells in response to LPS and PGN stimulation to levels compared with those in HC. Our findings indicate that chronic alcohol use alters the distribution as well as the phenotypic and functional characteristics of blood monocyte subsets, which are partially restored following 2 wk of alcohol withdrawal.